Carbon nanotube-modified sodium dodecyl sulfate-polyacrylamide gel electrophoresis for molecular weight determination of proteins - Parthasarathy, Meera; Debgupta, Joyashish; Kakade, Bhalchandra A.; Ansary, Abu Ayoobul; Khan, Mohammad Islam; Pillai, Vijayamohanan K. (Analytical Biochemistry, 2011)
The effect of incorporating carbon nanotubes (CNTs) in the gel matrix on the electrophoretic mobility of proteins based on their molecular weight differences was investigated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). More specifically, a reduction in standard deviation in the molecular weight calibration plots by 55% in the case of multiwalled carbon nanotubes (MWCNTs) and by 34% in the case of single-walled carbon nanotubes (SWCNTs) compared with that of pristine polyacrylamide gels was achieved after incorporating an insignificant amount of functionalized CNTs into the gel matrix. A mechanism based on a more uniform pore size distribution in CNT modified polyacrylamide gel matrix is proposed. Furthermore, the impact of SWCNTs and MWCNTs on the mobility of proteins in different molecular weight regimes at a given acrylamide concentration offers a tunable gel matrix in terms of the selection of molecular weight ranges of proteins. The robustness and excellent reproducibility of the CNT-PAGE protocol are expected to have a significant impact on the molecular weight determination of newly isolated proteins. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Carbon nanotubes; Gel electrophoresis; Molecular weight determination; Polyacrylamide; Protein separation

Competitive wetting of acetonitrile and dichloromethane in comparison to that of water on functionalized carbon nanotube surfaces - Debgupta, Joyashish; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Physical Chemistry Chemical Physics, 2011)
Differential wetting of pristine and ozonized carbon nanotubes has been studied using solvents like acetonitrile and dichloromethane in comparison to the well-known wetting behavior of water. Based on their unique structural and physical properties, functionalized CNT substrates have been used due to the fact that independent variation in molecular as well as electronic properties could be controlled by understanding the wetting of these liquids on carbon nanotubes (CNTs), both pristine as well as ozone treated. The sensitivity of the wetting behavior with respect to molecular interactions has been investigated using contact angle measurements while Raman and XPS studies unravel the differential wetting behavior. Charge-transfer between adsorbed molecules and CNTs has been identified to play a crucial role in determining the interfacial energies of these two liquids, especially in the case of acetonitrile. Ozone treatment has been observed to affect the surface properties of pristine CNTs along with a concomitant change in the wetting dynamics.

Electrochemical unzipping of multi-walled carbon nanotubes for facile synthesis of high-quality graphene nanoribbons - Shinde, Dhanraj B.; Debgupta, Joyashish; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of the American Chemical Society, 2011)
Here we report a remarkable transformation of carbon nanotubes (CNTs) to nanoribbons composed of a few layers of graphene by a two-step electrochemical approach. This consists of the oxidation of CNTs at controlled potential, followed by reduction to form graphene nanoribbons (GNRs) having smooth edges and fewer defects, as evidenced by multiple characterization techniques, including Raman spectroscopy, atomic force microscopy, and transmission electron microscopy. This type of ``unzipping'' of CNTs (single-walled, multi-walled) in the presence of an interfacial electric field provides unique advantages with respect to the orientation of CNTs, which might make possible the production of GNRs with controlled widths and fewer defects.

In situ electrochemical organization of CdSe nanoclusters on graphene during unzipping of carbon nanotubes - Debgupta, Joyashish; Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemical Communications, 2012)
In situ decoration of very small CdSe quantum dots on graphene nanoribbons (GNRs) has been achieved during the electrochemical unzipping of single walled carbon nanotubes. Critical parameters like the width of the GNRs, size distribution of quantum dots and their organization on GNRs have been shown to be strongly dependent on the electric field and time.

Laser synthesized super-hydrophobic conducting carbon with broccoli-type morphology as a counter-electrode for dye sensitized solar cells - Gokhale, Rohan; Agarkar, Shruti A.; Debgupta, Joyashish; Shinde, Deodatta; Lefez, Benoit; Banerjee, Abhik; Jog, Jyoti Prakash; More, Mahendra A.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Nanoscale, 2012)
A laser photochemical process is introduced to realize superhydrophobic conducting carbon coatings with broccoli-type hierarchical morphology for use as a metal-free counter electrode in a dye sensitized solar cell. The process involves pulsed excimer laser irradiation of a thin layer of liquid haloaromatic organic solvent o-dichlorobenzene (DCB). The coating reflects a carbon nanoparticle-self assembled and process-controlled morphology that yields solar to electric power conversion efficiency of 5.1% as opposed to 6.2% obtained with the conventional Pt-based electrode.

SHI irradiation induced effects in functionalized MWCNTs - Saikiran, V.; Pathak, A. P.; Rao, N. Srinivasa; Devaraju, G.; Debgupta, Joyashish; Kyriakou, I.; Emfietzoglou, D. (Radiation Effects and Defects in Solids, 2012)
Multi-walled carbon nanotubes (MWCNTs) have attracted extensive attention globally due to their applications in modern nanotechnology. It is very important to study the effects on these MWCNTs under swift heavy ion (SHI) irradiation since ion irradiation has been recognized as one of the best tools for nanostructuring of materials, in general. Here, we present the effects of 80MeV Ni ions with a fluence ranging from 3 x 10(12) to 3 x 10(13) ions/cm(2) on functionalized MWCNT mats. The properties of pristine and irradiated samples were studied using X-ray diffraction, Raman spectroscopy and transmission electron microscopy. The effects of SHI irradiation on these samples are discussed in detail.
Keywords: CNT; Raman; SHI; TEM

Thiolated graphene - a new platform for anchoring CdSe quantum dots for hybrid heterostructures - Debgupta, Joyashish; Pillai, Vijayamohanan K. (Nanoscale, 2013)
Effective organization of small CdSe quantum dots on graphene sheets has been achieved by a simple solution exchange with thiol terminated graphene prepared by diazonium salt chemistry. This generic methodology of CdSe QD attachment to any graphene surface has remarkable implications in designing hybrid heterostructures.

C@SiNW/TiO2 core-shell nanoarrays with sandwiched carbon passivation layer as high efficiency photoelectrode for water splitting - Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Shelke, Manjusha V. (Scientific Reports, 2014)
One-dimensional heterostructure nanoarrays are efficiently promising as high performance electrodes for photo electrochemical (PEC) water splitting applications, wherein it is highly desirable for the electrode to have a broad light absorption, efficient charge separation and redox properties as well as defect free surface with high area suitable for fast interfacial charge transfer. We present highly active and unique photoelectrode for solar H-2 production, consisting of silicon nanowires (SiNWs)/TiO2 core-shell structures. SiNWs are passivated to reduce defect sites and protected against oxidation in air or water by forming very thin carbon layer sandwiched between SiNW and TiO2 surfaces. This carbon layer decreases recombination rates and also enhances the interfacial charge transfer between the silicon and TiO2. A systematic investigation of the role of SiNW length and TiO2 thickness on photocurrent reveals enhanced photocurrent density up to 5.97 mA/cm(2) at 1.0 V vs. NHE by using C@SiNW/TiO2 nanoarrays with photo electrochemical efficiency of 1.17%.

Effect of self-assembly on triiodide diffusion in water based polymer gel electrolytes: an application in dye solar cell - Soni, S. S.; Fadadu, K. B.; Vekariya, R. L.; Debgupta, Joyashish; Patel, K. D.; Gibaud, A.; Aswal, Vinod K. (Journal of Colloid and Interface Science, 2014)
The preparation of ordered polymer gels from the amphiphilic block copolymers, Pluronic (R) F77, P123 and polyethylene glycol in the presence of ionic liquid, iodine and organic additives is presented. At 35%(w/w) concentration these copolymers (F77 and P123) self-assembled into cubic liquid crystalline phase in aqueous solution and characterized by using SAXS and AFM measurements. The effects of micellar aggregation formed by polymers on the ionic transport and triiodide diffusion have been studied by electro-chemistry and SANS experiments. The ionic migration or triiodide diffusion through these polymer gels is found to be affected by the PEO/PPO content in the polymer backbone. These gels were successfully employed as an electrolyte in a dye sensitized solar cell. A remarkable solar to electricity conversion efficiency and good stability was obtained using Pluronic (R) F77 based gel, which is attributed to its thermoreversible sol to gel transition. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Amphiphilic block copolymer; Dye solar cell; Micellar nanochannels; SANS; SAXS; Self-assembly; Water based gel electrolytes

Electrochemical preparation of vertically aligned, hollow CdSe nanotubes and their p-n junction hybrids with electrodeposited Cu2O - Debgupta, Joyashish; Devarapalli, Rami Reddy; Rahman, Shakeelur; Shelke, Manjusha V.; Pillai, Vijayamohanan K. (Nanoscale, 2014)
Vertically aligned, hollow nanotubes of CdSe are grown on fluorine doped tin oxide (FTO) coated glass substrates by ZnO nanowire template-assisted electrodeposition technique, followed by selective removal of the ZnO core using NH4OH. A detailed mechanism of nucleation and anisotropic growth kinetics of nanotubes have been studied by a combination of characterization tools such as chronoamperometry, SEM and TEM. Interestingly, ``as grown'' CdSe nanotubes (CdSe NTs) on FTO coated glass plates behave as n-type semiconductors exhibiting an excellent photo-response (with a generated photocurrent density value of similar to 470 mu A cm(-2)) white in contact with p-type Cu2O (p-type semiconductor, grown separately on FTO plates) because of the formation of a n-p heterojunction (type II). The observed photoresponse is 3 times higher than that of a similar device prepared with electrodeposited CdSe films (not nanotubes) and Cu2P on FTO. This has been attributed to the hollow 1-D nature of CdSe NTs, which provides enhanced inner and outer surface areas for better absorption of light and also assists faster transport of photogenerated charge carriers.

Homogeneous photochemical water oxidation by biuret-modified Fe-TAML: evidence of Fe-V(O) intermediate - Panda, Chakadola; Debgupta, Joyashish; Diaz, David Diaz; Singh, Kundan K.; Gupta, Sayam Sen; Dhar, Basab B. (Journal of the American Chemical Society, 2014)
{Water splitting, leading to hydrogen and oxygen in a process that mimics natural photosynthesis, is extremely important for devising a sustainable solar energy conversion system. Development of earth-abundant, transition metal-based catalysts that mimic the oxygen-evolving complex of photosystem II, which is involved in oxidation of water to O-2 during natural photosynthesis, represents a major challenge. Further, understanding the exact mechanism, including elucidation of the role of active metal-oxo intermediates during water oxidation (WO), is critical to the development of more efficient catalysts. Herein, we report Fe-III complexes of biuret-modified tetra-amidomacrocyclic ligands (Fe-TAML; 1a and 1b) that catalyze fast, homogeneous, photochemical WO to give OD with moderate efficiency (maximum TON = 220

Photophysical and photoconductivity properties of thiol-functionalized graphene-CdSe QD composites - Debgupta, Joyashish; Mandal, Sadananda; Kalita, Hemen; Aslam, Mohammed; Patra, Amitava; Pillai, Vijayamohanan (RSC Advances, 2014)
Graphene-semiconductor QD hybrid nanostructure materials have recently emerged as a new class of functional materials because of their potential applications in solar energy conversion, optoelectronic devices, sensing etc. Here, oleic acid-capped CdSe QDs are attached to -PhSH functionalized graphene by ligand exchange via bonding with the -SH group. The shifting of the G-band and D-band due to structural changes for the attachment of QD with graphene has been evaluated by using Raman spectroscopy. Steady state photoluminescence (PL) and time resolved fluorescence measurements have been employed to understand the electronic interactions between graphene and CdSe QDs. A time resolved fluorescence spectroscopic study has been used to understand the fluorescence dynamics of the photoexcitated CdSe QDs in the presence of graphene. It is evident that the electron transfer occurs from photoexcited QDs to graphene and the electron transfer rate is found to be 12.8 x 10(8) s(-1) for 3.8 nm CdSe QDs. Photoconductivity properties of the graphene-QD device under illumination have been examined and it is to be noted that 2-3 fold increase in the photocurrent is found in this composite device in presence of 1.5 AM solar simulated light. The enhancement of the photocurrent in this hybrid device is found to be suitable for potential applications in optoelectronic and solar cell systems.

Co3O4 nanorods-efficient non-noble metal electrocatalyst for oxygen evolution at neutral pH - Ramsundar, Rani M.; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Joy, Pattayil Alias (Electrocatalysis, 2015)

Comparative study of dG affinity vs. DNA methylation modulating properties of side chain derivatives of procainamide: insight into its DNA hypomethylating effect - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Debgupta, Joyashish; Sangtani, E.; Narwade, S.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Deobagkar, D. D. (RSC Advances, 2016)
Procainamide derivatives have been synthesized to investigate the role of side chains in modulating the DNA methylation level in cancer cells and gain insight into its mechanism of action. The synthesized derivatives comprised of flexible (dimethyl), constrained (pyrrolidine, piperidine, morpholine) and planar aromatic (pyridine, phenyl) side chain motifs. The affinity of procainamide and its derivatives towards the deoxyguanosine (dG) base in neutral form has been assessed by performing Differential Pulse Voltammetry (DPV) under physiological conditions. Further, molecular docking with hemimethylated CpG rich DNA acquired from an active mDNMT-1-DNA (PDB ID-4DA4) crystal structure, reveals their preferential non-covalent interaction with dG nucleobase in the intercalation cavity of the minor groove. Differential affinity of the derivatives to dG base in neutral and bound forms (DNA) is correlated with their DNA methylation modulating properties at sub-lethal concentrations. Among all the derivatives, a compound with an aromatic phenyl side chain (1) has shown a highest binding affinity for dG nucleobase in neutral form as well as for partially denatured CpG rich DNA which is attributed to the formation of p/p stacking interaction in addition to N-H/O hydrogen bonding with the pyrimidine ring of dG base. It also shows the highest cytotoxicity and global hypomethylation at a sub-lethal level in the MCF-7 cancer cell line compared to other derivatives and procainamide. A docking study has also illustrated the plausible structural basis of DNA methylation modulating a property of procainamide. Strong association of procainamide with dG bases of partially denatured CpG rich DNA via H-bonding and other non-covalent interactions may alter the active topology of DNA required by the DNA-binding regulatory proteins (e. g. DNMT-1) which is validated by a DNMT-1 inhibition assay. This systematic investigation leads to a new potent alternative to procainamide being found and gives a plausible insight into the DNA hypomethylating effect of procainamide.

Facile green synthesis of BCN nanosheets as high-performance electrode material for electrochemical energy storage - Karbhal, Indrapal; Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shelke, Manjusha V. (Chemistry-A European Journal, 2016)
Two-dimensional hexagonal boron carbon nitride (BCN) nanosheets (NSs) were synthesized by new approach in which a mixture of glucose and an adduct of boric acid (H3BO3) and urea (NH2CONH2) is heated at 900 degrees C. The method is green, scalable and gives a high yield of BCN NSs with average size of about 1 mm and thickness of about 13 nm. Structural characterization of the as-synthesized material was carried out by several techniques, and its energy-storage properties were evaluated electrochemically. The material showed excellent capacitive behaviour with a specific capacitance as high as 244 F g(-1) at a current density of 1 A g(-1). The material retains up to 96% of its initial capacity after 3000 cycles at a current density of 5 A g(-1).
Keywords: boron; Doping; Electrochemistry; Nanoparticles; nitrides

Synthesis of novel Cu2S nanohusks as high performance counter electrode for CdS/CdSe sensitized solar cell - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Dave, Yasha; Debgupta, Joyashish; Shelke, Manjusha V. (Journal of Power Sources, 2016)
An important component of quantum dot sensitized solar cells (QDSSC) is the counter electrode which mediates the regeneration of oxidized quantum dots by reducing the polysulphide electrolyte. However, design and synthesis of an efficient counter electrode material is a challenging task. Herein, we report the synthesis of a unique Cu2S nanohusks directly on FTO coated glass substrates by electrodeposition and used as a counter electrode in QDSSC. When these electrodes are used for the reduction of polysulfide electrolyte in QDSSC, they exhibit higher catalytic activity and photovoltaic performance as compared to the Platinum counter electrode. The power conversion efficiency of about 4.68% has been achieved by optimizing the deposition time of Cu2S. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: counter electrode; Cu2S electrodeposition; Cu2S nanohusks; Quantum dot-sensitized solar cell

Electrochemical water oxidation catalyzed by an in situ generated alpha-Co(OH)(2) film on zeolite-Y surface - Bose, Suranjana; Debgupta, Joyashish; Ramsundar, Rani M.; Das, Samar K. (Chemistry-A European Journal, 2017)
The design and synthesis of an efficient and robust water-oxidation catalyst with inexpensive materials remains an important challenge in the context of artificial photosynthesis. Herein, a simple but unique technique is reported to in situ generate a thin-film of alpha-Co(OH)(2) on the surface of zeolite-Y [hereafter referred to as Y-alpha-Co(OH)(2)] that acts as an efficient and stable catalyst for electrochemical water oxidation in alkaline medium. Catalyst Y-alpha-Co(OH)(2) is so stable that it retains its catalytic activity even after 2000 cyclic voltammetric cycles of water oxidation. Expectedly, the chemical composition of alpha-Co(OH)(2) on the surface of zeolite-Y remains same as that of parent Y-alpha-Co(OH)(2) after 2000 electrocatalytic cycles. A Tafel slope as low as 59 mV decade(-1) in 0.1m KOH (pH 13) suggests faster oxygen evolution kinetics (overpotential = 329 mV; turnover frequency = 0.35 mol O-2 (mol Co)(-1)s(-1) at 1 mA cm(-2)) than the existing alpha-Co(OH)(2)-based electrocatalysts operating in alkaline medium.